(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the effectiveness of Fu’s subcutaneous needling (FSN) combined with acupressure massage therapy in treating Cervical scapulohumeral syndrome due to cervical spondylosis. Subjects and methods: A clinical trial study, comparing before and after treatment, with a control group. 80 patients were divided into 2 groups: the research group treated with FSN combined with acupressure massage and the control group treated with Electro-acupuncture combined with acupressure massage. Results: Pain relief effect: average pain score according to the VAS scale decreased from 5.23 ± 0.73 points to 1.03 ± 0.97 points, statistically significant with p < 0.01 and better than the control group (p < 0.05). The score of limited range of motion of the cervical spine decreased from 16.13 ± 3.38 points to 1.05 ± 2.27 points, statistically significant with p < 0.01 and improved better than the control group with p<0.05. Effective in improving radicular syndrome: after treatment, the rate of radicular syndrome decreased from 100% to 15%, statistically significant with p < 0.01 and equivalent to the control group (p> 0.05). Conclusion: The combination of Fu’s subcutaneous needling and acupressure massage therapy is effective in treating Cervical scapulohumeral syndrome due to cervical spondylosis through pain reduction, improvement in cervical spine motion range, and improvement in root syndrome better than control group.